Endemism Patterns of Planthoppers (Fulgoroidea) in China - Zhao, Zhengxue; Yang, Lin; Long, Jiankun; Chang, Zhimin; Zhou, Zhengxiang; Zhi, Yan; Yang, Liangjing; Li, Hongxing; Sui, Yongjin; Gong, Nian; Wang, Xiaoya; Chen, Xiangsheng (Frontiers in Ecology and Evolution, 2021)
Studies on endemism are always of high interest in biogeography and contribute to better understanding of the evolution of species and making conservation plans. The present study aimed to investigate the endemism pattern of planthoppers in China by delimiting centers of endemism and areas of endemism. We collected 6907 spatial distribution records for 860 endemic planthopper species from various resources. Centers of endemism were identified using a 1° grid size. Parsimony analysis of endemicity and endemicity analysis were employed to detect areas of endemism at 1°, 1.5°, and 2° grid sizes. Six centers of endemism located in mountainous areas were identified: Taiwan Island, Hainan Island, eastern Yungui Plateau, Wuyi Mountains, western Qinling Mountains, and western Yunnan. We also delimited six areas of endemism, which were generally consistent with centers of endemism. Our findings demonstrated that mountainous areas have an essential role in facilitating the high level of endemism and formation of areas of endemism in planthoppers through the combined effects of complex topography, a long-term stable environment, and geological events. Dispersal ability and distribution of host plants also have important effects on the patterns of planthoppers’ endemism.